Severe dilated cardiomyopathy as an unusual clinical presentation in an infant with sialidosis type II - Margot Eyskens; Luc Bruyndonckx; André B. P. Van Kuilenburg; François Eyskens (JIMD Reports, 2023)
Abstract We report a unique case of an infant with a severe dilated cardiomyopathy as the clinical presentation of sialidosis type II (OMIM 256550), a rare autosomal recessive inherited lysosomal storage disease that is characterized by partial or complete deficiency of α‐neuraminidase, following mutations in the gene neuraminidase 1 (NEU1), located on the short arm of chromosome 6 (6p21.3). Accumulation of metabolic intermediates leads to severe morbidity, especially myoclonus, gait disturbances, cherry‐red macules with secondary loss of visual acuity, impaired color vision and night blindness, and sometimes additional neurological findings such as seizures. Dilated cardiomyopathies are characterized by dilation and impaired contraction of the left or both ventricles, whereas most of the metabolic cardiomyopathies are hypertrophic forms appearing with diastolic dysfunction and, in case of lysosomal storage diseases, often associated with valvular thickening and prolapse. Cardiac manifestations in systemic storage disorders are common although rarely described in mucolipidoses. In mucolipidosis type 2 or I‐cell disease only three cases were presented with severe dilated cardiomyopathy and endocardial fibroelastosis in infancy, as opposed to sialidosis type II, by which to the best of our knowledge no presentation of dilated cardiomyopathy was previously reported in literature.